Genetic data from algae sedimentary DNA reflect the influence of environment over geography - Stoof-Leichsenring, Kathleen R. (Dr.); Herzschuh, Ulrike (Prof. Dr.); Pestryakova, Luidmila A. (Prof. Dr.); Klemm, Juliane; Epp, Laura Saskia; Tiedemann, Ralph (Prof. Dr.) (Scientific Reports, 2015)
Genetic investigations on eukaryotic plankton confirmed the existence of modern biogeographic patterns, but analyses of palaeoecological data exploring the temporal variability of these patterns have rarely been presented. Ancient sedimentary DNA proved suitable for investigations of past assemblage turnover in the course of environmental change, but genetic relatedness of the identified lineages has not yet been undertaken. Here, we investigate the relatedness of diatom lineages in Siberian lakes along environmental gradients (i.e. across treeline transects), over geographic distance and through time (i.e. the last 7000 years) using modern and ancient sedimentary DNA. Our results indicate that closely-related Staurosira lineages occur in similar environments and less-related lineages in dissimilar environments, in our case different vegetation and co-varying climatic and limnic variables across treeline transects. Thus our study reveals that environmental conditions rather than geographic distance is reflected by diatom-relatedness patterns in space and time. We tentatively speculate that the detected relatedness pattern in Staurosira across the treeline could be a result of adaptation to diverse environmental conditions across the arctic boreal treeline, however, a geographically-driven divergence and subsequent repopulation of ecologically different habitats might also be a potential explanation for the observed pattern.